2020
DOI: 10.1111/1742-6723.13591
|View full text |Cite
|
Sign up to set email alerts
|

Does location of rapid influenza diagnostic testing influence treatment time and ancillary testing in a paediatric emergency department?

Abstract: Objective Influenza causes a significant burden of disease. Our aim was to assess whether location of rapid influenza diagnostic testing (RIDT) for patients with influenza‐like illness (ILI) has an impact on ED treatment time or ancillary testing. Methods This was a retrospective observational study in a tertiary paediatric ED during 2017 influenza season. All patients with ILI were included. Some had RIDT performed (ED bedside or at the laboratory). Primary outcome measure was the correlation of RIDT location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 19 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…Such social values are also recognised by our participants, illustrating how test results can curb the insecurities of less experienced doctors, strengthen their credibility in dialogue with senior colleagues and care seekers, help them gain clinical expertise, and increase care seeker satisfaction. At the same time, clinically unjustified testing adds to the workload of the personnel and subjects children to procedures deemed invasive enough to be uncomfortable to them [35,36. Also, reports of over-reliance on technology as a cause of de-skilling clinicians are echoed by our findings stating that doctors would need to rely more on their clinical skills in the scenario in which POCTs are not available to them [5,10,26,37].…”
mentioning
confidence: 71%
“…Such social values are also recognised by our participants, illustrating how test results can curb the insecurities of less experienced doctors, strengthen their credibility in dialogue with senior colleagues and care seekers, help them gain clinical expertise, and increase care seeker satisfaction. At the same time, clinically unjustified testing adds to the workload of the personnel and subjects children to procedures deemed invasive enough to be uncomfortable to them [35,36. Also, reports of over-reliance on technology as a cause of de-skilling clinicians are echoed by our findings stating that doctors would need to rely more on their clinical skills in the scenario in which POCTs are not available to them [5,10,26,37].…”
mentioning
confidence: 71%
“…Included studies were published between 2002 [ 28 ] and 2021 [ 13 , 25 ]. Eight of eighteen studies were randomised control trials [ 17 , 18 , 19 , 20 , 22 , 23 , 24 , 25 ], three were prospective cohort studies [ 14 , 15 , 26 ], five were retrospective cohort studies [ 8 , 12 , 21 , 27 , 28 ], one was a before and after interventional study [ 16 ], and one was a pragmatic AB single subject study [ 13 ]. The studies were conducted in several different countries, the majority being in the United States [ 8 , 12 , 16 , 18 , 20 , 22 , 24 , 25 , 26 , 27 , 28 ], but also other countries including United Kingdom [ 13 ], Canada [ 17 ], Australia [ 21 ], Belgium [ 14 ], Brazil [ 15 ], Italy [ 19 ] and Turkey [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…All included studies were conducted in the ED of a paediatric hospital or within the paediatric population of a general hospital, however, the number of hospitals varied between studies. Fifteen of eighteen studies reported outcomes from the paediatric population only [ 8 , 12 , 13 , 15 , 16 , 17 , 19 , 20 , 21 , 23 , 24 , 25 , 26 , 27 , 28 ], and three studies extracted paediatric data from a general hospital [ 14 , 18 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations